Evaluation of elite soybean genotypes for yield and rust resistance in Southern Zone of India: Evaluation of elite soybean genotypes for yield and rust resistance in Southern Zone of India - G K NAIDU; SHALINI N HUILGOL; G SOMANAGOUDA; R CHANNAKESHAVA; HARSHIYA BANU; G T BASAVARAJA; SANJAY GUPTA (Journal of Oilseeds Research, 2023)
The genotype x environment interaction (GEI) is an important aspect of plant breeding program as it decides the general and specific adaptation of a variety to the varied environments. Higher magnitude of GEI were noted in soybean with significant influence on yield. In the present study fourteen genotypes were evaluated at six locations in Southern Zone of India (Adilabad, Bangalore, Bidar, Dharwad, Kasbe Digraj and Pune) during Kharif 2017, 2018 and 2019. Across locations, DSb 34 recorded 21 % and 18 % increased yield over zonal check (DSb 21) and rust susceptible check (JS 335), respectively. DSb 34 also exhibited highly resistant reaction to rust disease at hotspot location and can be used as donor in soybean disease resistance improvement.